Inter-annual morphometric assessment of fin whales (Balaenoptera physalus) based on drone photogrammetry - Mészáros, Dorottya (2023)
Morphometrics such as length, body proportions, and volume are reliable data to determine the foraging success, energy reserve accumulation, and individual fitness, furthermore, it informs upon the population status of the examined species. Unmanned aerial vehicles (UAV) provides a new, low-cost, non-invasive platform to execute photogrammetric studies on free-ranging Cetaceans, enabling quantitative assessment of temporal and permanent changes of the animal's body. The aims of this study were to accumulate accurate morphometric measurements of fin whales (Balaenoptera physalus) in the Catalan coast, to compute growth trends of several body proportions, assess the evolution of body area index and body volume over time, and to compare these parameters within three consecutive foraging seasons. In total, 1099 still images were measured during this project, depicting 82 individual fin whales from three years between 2021 and 2023. The obtained results indicate that there were strong correlations among the growth trend of certain body parameters. The most significant correlation was between the total length of the body and the eye-to-eye distance. It was determined that in some cases the growth ratios can be further influenced by the gender and the size of the whale. Moreover, measures of three resighted individuals showed moderate increase of the body length and four animals showed gradual positive progression of the body area index and body volume within and over the three seasons, demonstrating foraging success and energy reserve accumulation. In a more general scale, smaller animals displayed the highest body area index, while the largest ones exhibit the lowest measures. The present study illustrates the utility of drone-based photogrammetry to detect and assess temporal and permanent changes in the body parameters of fin whales in the Garraf coast.